Land use change implications on community spirit of place the rezoning of Maginhawa St. towards urban regeneration - Tablante, Ivy Sychelle B.; Mata, Rene Luis S. (Quezon City College of Architecture, University of the Philippines Diliman, 2015)
As urban areas evolve through time, land use change may take place. Simultaneously, effects on the physical environment and community identity occur. A land use change example is the transformation of zones from residential to commercial. This is commonly seen in Metropolitan Manila, where urban areas, both planned and unplanned, continuously transform to meet the ever-changing needs of the people. This study primarily intends to determine how an emergent community identity effected by residential to commercial rezoning contributes to the regeneration of that community. It documents the physical, economic, and socio-cultural manifestations of this transformation, which affect, alter, or create identity. Exploring the importance of place making in urban regeneration, the study aims to start a discussion on the role of the existence of a strong "spirit of place" in place making as a dominant quality of great communities worldwide. To achieve these objectives, the study will review the history of land use and the present configuration of zones along Maginhawa Street in Quezon City. Focus group discussions and informal interviews will be used in the absence of historical data. Secondary date, photomapping, and questionnaires will be used to determine identity perception before and after land use change. This study postulates that land use change, especially residential to commercial rezoning, directly affects the community's perception of its character. The effects of such change have the ability to enrich an existing spirit of place, or create an entirely new one. This identity enrichment is considered to be an important component of local revitalization that can contribute to urban regeneration. Awareness of such role of a strong spirit of place in urban regeneration is vital in inspiring future urban designs that provide spatial and social opportunities for the creation or enrichment of community character; and important in identifying existing planned/unplanned communities that can benefit from a revitalization identity. Keywords: commercial, community identity, land use, land use change, residential, spirit of place, urban regeneration.
Includes appendices
Thesis (Master of Architecture)-- University of the Philippines, Diliman